Menggugat Peran Wali Nikah: Potret Bias Gender & Analisa Fikih Egalitas - Yusuf, M. (Sunan Kalijaga State Islamic University & The Asia Foundation, 2007)
Islamic society will always be practically encircled by patriarchal culture and male domination if the body of Islamic laws does not offer the solution to the problem. As long as the patriarchal values dominate all legal considerations taken into account the formulation of law produced will be male biased and subordinate women. As a result, Islam as a religion will appear to be unfriendly to women -a situation which is against its own spirit. This present article aims to discuss the issue of wali in a marriage contract by applying a structuralism method within linguistic paradigm and critical historical approach. Using these methods, the author argues that the mainstream views of Islamic law on wali are gender,biased and unfair to women. Because gender injustice is against the spirit of Islam, the patriarchal fiqh should be re-examined and replaced by the egalitarian Islamic law.